THE PRIORITY NEEDS IN DEVELOPING ACADEMIC MANAGEMENT OF SURASAKMONTREE SCHOOL BASED ON THE CONCEPT OF ARTIFICIAL INTELLIGENCE LITERACY - Lupholthae , Eakanat; Jariyarangsiroge , Apiradee (Journal of Educational Review Faculty of Education in MCU, 2025)
This research article aimed to: 1) examine the current and desired states of academic management at Surasakmontree School based on the concept of Artificial Intelligence (AI) Literacy, and 2) investigate the needs for the development of academic management aligned with AI Literacy. The study employed a descriptive research methodology. The sample consisted of 111 participants, including school administrators and teachers. Purposive sampling was used to select 2 administrators and 9 heads of learning areas, while 100 teachers were selected through simple random sampling. The research instrument was a questionnaire validated for content accuracy by experts using the Item-Objective Congruence (IOC) method and tested for reliability, yielding a Cronbach’s alpha coefficient of 0.98. Data were analyzed using mean, standard deviation, and the Modified Priority Needs Index (PNImodified). The research findings revealed that: (1) the current state of academic management based on AI Literacy was rated at a low level, whereas the desired state was at a high level and (2) regarding the needs for development, the highest need was in curriculum development (PNImodified = 0.872), followed by instructional process development (PNImodified = 0.674), and assessment and evaluation (PNImodified = 0.658), respectively. When considering AI Literacy components, the greatest need was found in the area of learning and understanding AI (PNImodified = 0.979), followed by AI ethics (PNImodified = 0.788), AI evaluation (PNImodified = 0.769), and AI usage and application (PNImodified = 0.743). The findings suggest that schools should prioritize systematic integration of AI into their curriculum to enhance students’ AI Literacy, encompassing knowledge, practical skills, evaluation, and ethical awareness. The results can serve as a guideline for academic management planning to promote AI Literacy among students.